2024
DOI: 10.1002/acr.25252
|View full text |Cite
|
Sign up to set email alerts
|

Causal Factors for Osteoarthritis: A Scoping Review of Mendelian Randomization Studies

Eaman Alhassan,
Kevin Nguyen,
Marc C. Hochberg
et al.

Abstract: BackgroundMendelian randomization (MR) has increasingly been utilized as a tool for establishing causal relations between modifiable exposures and osteoarthritis (OA).ObjectiveThe goal of this review was to summarize available MR studies of OA that evaluate the causal role of modifiable risk factors on OA.MethodsThis review was performed following the PRISMA‐ScR (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses Extension for Scoping Reviews) model. We performed a literature search for relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The following information was gathered using a household structured questionnaire: age (20-44, 45-64, ≥ 65 years), gender (male and female), race (Mexican American, Other Hispanic, Non-Hispanic white, Non-Hispanic black and Other race), level of education (less than high school, high school, more than high school), Examination data included BMI (kg/m2). Laboratory data covered blood urea nitrogen (BUN, mmol/L) 12 , total calcium (Ca, mmol/L) 13 , phosphorus (P, mmol/L) 14 , triglycerides (TG, mmol/L) 15 , uric acid (UA, µmol/L) 16 , and total cholesterol (TC, mmol/L) 17 . As a nal point, questionnaire data included information on smoking behavior (Yes/No) 18 , alcohol consumption (Yes/No) 19 , hypertension (Yes/No) 20 , and diabetes (Yes/No) 21 .…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…The following information was gathered using a household structured questionnaire: age (20-44, 45-64, ≥ 65 years), gender (male and female), race (Mexican American, Other Hispanic, Non-Hispanic white, Non-Hispanic black and Other race), level of education (less than high school, high school, more than high school), Examination data included BMI (kg/m2). Laboratory data covered blood urea nitrogen (BUN, mmol/L) 12 , total calcium (Ca, mmol/L) 13 , phosphorus (P, mmol/L) 14 , triglycerides (TG, mmol/L) 15 , uric acid (UA, µmol/L) 16 , and total cholesterol (TC, mmol/L) 17 . As a nal point, questionnaire data included information on smoking behavior (Yes/No) 18 , alcohol consumption (Yes/No) 19 , hypertension (Yes/No) 20 , and diabetes (Yes/No) 21 .…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…Over the last decade, a plethora of MR studies have been undertaken to pinpoint causal factors linked to OA. For instance, MR investigations have offered backing for causal relationships between OA and elevated adiposity, coffee intake, bone mineral density, and sleep disruption, alongside diminished levels of serum calcium and low-density lipoprotein cholesterol [ 30 ]. These findings emphasize the potential advantages of decreasing weight and enhancing sleep quality to lower the risk of OA, while also highlighting the necessity for gaining a deeper understanding of the correlation between coffee intake and serum calcium concentrations regarding OA risk.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Recent MR studies support a causal relationship between OA and lifestyle-related obesity, coffee intake, Bdensity, sleep disturbance, decreased serum calcium and LDL cholesterol levels. [ 7 ] No studies have reported using MR methods to test the causal effect of dried fruit intake and OA risk. Therefore, this study used a two-sample MR analysis to investigate whether dried fruit intake is causally associated with the risk of developing OA.…”
Section: Introductionmentioning
confidence: 99%